2018
DOI: 10.1530/ec-18-0207
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D measurement and effect on outcome in a cohort of patients with heart failure

Abstract: ObjectivesThe aims of this paper were to evaluate the levels of Vitamin D (VitD) in patients with heart failure (HF), compared to a control group, to assess the effects of VitD on HF outcome and to compare VitD measurement between LIAISON immunoassay and HPLC-MS-MS methods in this population.Design and MethodsWe collected clinical, biochemical and outcome data from 247 patients with HF and in a subgroup of 151 patients, we measured VitD both with LIAISON and HPLC-MS-MS.ResultsHF patients had statistically lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
2
6
0
1
Order By: Relevance
“…In our study, the mean serum values of 25-OH-D 3 were significantly lower in heart failure patients compared to CON (20.49 ± 7.31 vs. 37.09 ± 4.59 ng/mL, p < 0.001), as confirmed in previous studies [23,24]. Multiple regression analysis by the Enter method considering 25-OH D3 as dependent variable demonstrated indicators of vascular stiffness RRI ( p = 0.004) and c-f PWV ( p = 0.005) as predictors, suggesting that vitamin D deficit might contribute to increased vascular stiffness in heart failure (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the mean serum values of 25-OH-D 3 were significantly lower in heart failure patients compared to CON (20.49 ± 7.31 vs. 37.09 ± 4.59 ng/mL, p < 0.001), as confirmed in previous studies [23,24]. Multiple regression analysis by the Enter method considering 25-OH D3 as dependent variable demonstrated indicators of vascular stiffness RRI ( p = 0.004) and c-f PWV ( p = 0.005) as predictors, suggesting that vitamin D deficit might contribute to increased vascular stiffness in heart failure (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…Our group recently reported results from an Italian cohort of 261 patients with HF in whom low serum levels of 25OHD were inversely correlated with a validated score of HF mortality, namely the Metabolic Exercise Cardiac Kidney Index or MECKI score [126]. In a subgroup of these patients, cardiovascular outcomes have been also reported: patients with HF had mean serum levels of 25OHD statistically lower than healthy subjects (45.2 ± 23.7 nmol/L vs. 58.2 ± 24.0 nmol/L, p < 0.001) and a higher prevalence of vitamin D insufficiency (serum 25OHD < 50 nmol/L or 20 ng/mL) (61.1% vs. 39.5%, p < 0.001), associated with higher mortality risk [127].…”
Section: Pleiotropic Effects Of Vitamin Dmentioning
confidence: 92%
“…Most of the risk factors for HFrEF in Western populations have been described in association with ischemic heart disease [15]. It has been proposed that vitamin D might play a role in disease pathogenesis, as serum 25(OH)D levels have been demonstrated to be lower in patients with HF compared with control subjects [16]. Specifically, prospective studies have shown that the risk of developing HF is increased in patients with vitamin D deficiency [17].…”
Section: Introductionmentioning
confidence: 99%